Mixed FEM for quantum nanostructured solar cells. (1st December 2019) - Sladek, Jan; Sladek, Vladimir; Repka, Miroslav; Schmauder, Siegfried
Abstract: The gradient theory of piezoelectricity is developed for 3D analyses of QDs with the functionally graded lattice mismatch between the QD and the matrix. Governing equations in the gradient theory contain higher order derivatives than in conventional approaches. Then, it is needed to apply the C 1 -elements for approximation of primary fields in the FEM. The mixed FEM with the C 0 continuous interpolation and collocation approach for kinematic constraints between strains and displacements is developed. The high-density arrays of quantum dots requires to consider various sizes for the representative volume element of the nanostructured solar cell created by the QD (InAs) and matrix (GaAs).